A Literature Review of Indonesian Students' Mathematical Communication Ability in Geometry Materials - Rayinda Khaerul Wiladah Bahrun; Dadan Dasari (EduLine: Journal of Education and Learning Innovation, 2023)
The purpose of this study is to identify and examine students' written mathematical communication skills in geometry subject over the last five years. This study is a literature review that was conducted by looking for and assessing similar previous studies. Several stages were completed in this research: (1) identifying articles that discussed communication skills in geometry material, (2) analyzing student mathematical communication abilities in working geometry questions, and (3) identifying similarities in mathematical communication inhibiting factors. According to the findings of the study's six articles, pupils had difficulties articulating ideas, mathematical circumstances in writing with visuals, and algebra, expressing ideas or mathematical situations in everyday life in algebraic form. Students' mathematical communication abilities have not achieved their full potential. Of course, there are numerous elements that influence this, including pupils' lack of desire to describe or comprehend the challenges or problems they confront. Students do not understand the fundamental principles involved in answering these questions. Some pupils also do not understand the context of the questions, resulting in carelessness factor in communicating it mathematically.